(untitled) (Research, Society and Development, 2020)
The insertion of Information and Communication Technologies (ICT) at school brought huge challenges to teachers because those see its use in classroom as a big problem. The use in visual means, communicatives, dynamics and innovative, in other hand, has awakened the students’ interesting in Sciences class and therefore bringing a knowledge increase. In this view, this essay aimed to discuss the ITC relations in school environment and if the use of these resources improve the teaching in Sciences class promoting a significant learning. The data collection was done in a training course where 62 Science teachers answered a questionnaire about ITC in the classes. Among the aspects mentioned by the teachers, the training to the use of technologies and the lack of equipments in good conditions are the main setbacks to not use the ITC in classes. Despite being a welcoming methodology by students and teachers, there isn’t incentive, support and infrastructure to be well used and then, contribute to a knowledge scientific building in basic education.